Caffeinated Beverage Intake, Dyspnea With Ticagrelor, and Cardiovascular Outcomes: Insights From the PEGASUS‐TIMI 54 Trial. Issue 10 (18th May 2020) - Furtado, Remo H. M.; Venkateswaran, Ramkumar V.; Nicolau, Jose C.; Gurmu, Yared; Bhatt, Deepak L.; Storey, Robert F.; Steg, P. Gabriel; Magnani, Giuglia; Goto, Shinya; Dellborg, Mikael; Kamensky, Gabriel; Isaza, Daniel; et al.
Abstract : Background: A proposed cause of dyspnea induced by ticagrelor is an increase in adenosine blood levels. Because caffeine is an adenosine antagonist, it can potentially improve drug tolerability with regard to dyspnea. Furthermore, association between caffeine and cardiovascular events is of clinical interest. Methods and Results: This prespecified analysis used data from the PEGASUS TIMI 54 (Prevention of Cardiovascular Events in Patients With Prior Heart Attack Using Ticagrelor Compared to Placebo on a Background of Aspirin–Thrombolysis in Myocardial Infarction 54) trial, which randomized 21 162 patients with prior myocardial infarction to ticagrelor 60 mg or 90 mg or matching placebo (twice daily). Baseline caffeine intake in cups per week was prospectively collected for 9694 patients. Outcomes of interest included dyspnea, major adverse cardiovascular events (ie, the composite of cardiovascular death, myocardial infarction, or stroke), and arrhythmias. Dyspnea analyses considered the pooled ticagrelor group, whereas cardiovascular outcome analyses included patients from the 3 randomized arms. After adjustment, caffeine intake, compared with no intake, was not associated with lower rates of dyspnea in patients taking ticagrelor (adjusted hazard ratio (HR), 0.91; 95% CI, 0.76–1.10; P =0.34). There was no excess risk with caffeine for major adverse cardiovascular events (adjusted HR, 0.78; 95% CI, 0.63–0.98; P =0.031), sudden cardiac death (adjusted HR, 0.98; 95% CI, 0.57–1.70; P =0.95), or atrial fibrillation (adjusted odds ratio, 1.07; 95% CI, 0.56–2.04; P =0.84). Conclusions: In patients taking ticagrelor for secondary prevention after myocardial infarction, caffeine intake at baseline was not associated with lower rates of dyspnea compared with no intake. Otherwise, caffeine appeared to be safe in this population, with no apparent increase in atherothrombotic events or clinically significant arrhythmias. Registration: URL: https://www.clini​caltr​ials.gov ; Unique identifier: NCT01225562.